CAN COPE BECOME A PERMANENT MEDICAID SERVICE? PERSPECTIVES FROM INTERVENTIONISTS AND CARE MANAGERS. (11th November 2018) - Robison, J; McAbee-Sevick, H; Kellett, K; Fortinsky, R H; Gitlin, L
Abstract: An important aspect of the COPE CT study translational design is understanding implementation processes to enable widespread adoption within the CT Home Care Program for Elders (CHCPE) and programs elsewhere. Normalization Process Theory (NPT) posits specific criteria for judging implementation potential of an intervention, how the intervention may affect practice settings, and how it can be modified to support its implementation. Focus groups designed in accordance with NPT are conducted annually with CHCPE care managers and COPE interventionists. We present findings from the 2 interventionist (OT/APRN) and the 6 care manager focus groups held during study years 3 and 4, focusing on how to permanently integrate COPE into CHCPE. Participants strongly endorsed making the program a permanent service option, delineating the ways families have benefitted from the program. They noted potential challenges such as care plan budget limitations and how to deliver COPE to clients without involved families.